Atypical phenotype and response of B cells in patients with seropositive rheumatoid arthritis (2021)
ABSTRACT: Patients with rheumatoid arthritis (RA) may be classified as seropositive or seronegative according to the presence of autoantibodies. An abnormal B cell phenotype and function could be one of the main components of the immunopathology of seropositive patients; however, there is little information regarding B cell defects in these patients. This study shows a broad characterization of the B cell phenotype and function in patients with seropositive RA. We focused mainly on the evaluation of subsets, the expression of modulatory molecules of cell activation (CD22, FcɣRIIb and FcµR), calcium mobilization, global tyrosine phosphorylation, expression of activation markers, cytokine and immunoglobulin (Ig) production, proliferation and the in-vitro generation of plasma cells. Increased frequency of CD27- IgM- IgD- and CD21- B cells was observed in patients with seropositive RA compared with healthy donors (HD). Decreased expression of CD22 was primarily found in memory B cells of patients with RA regardless of seropositivity. B cells from seropositive patients exhibited normal proliferation, calcium mobilization kinetics and global tyrosine phosphorylation, but showed an increased frequency of CD86+ B cells compared with HD. B cells of seropositive patients secrete less interleukin-10 after in-vitro activation and showed a decreased frequency of plasma cell differentiation and IgM production compared with HD. Our data indicate that patients with seropositive RA have an increased frequency of atypical B cell populations previously associated with chronic activation and antigen exposure. This may result in the observed low responsiveness of these cells in vitro.